On the Strength and Crack Propagation Process of the Pre-Cracked Rock-Like Specimens under Uniaxial Compression - Haeri, H.; Shahriar, K.; Marji, M.F.; Moarefvand, P. (Проблемы прочности, 2014)
The pre-cracked cylindrical specimens of rocklike materials are experimentally tested under compressive loading (using specially made rock-like specimens from portland pozzolana cement (PPC)).The stress-strain and strength of the specimens are measured showing the decreasing effects of the cracks and their orientation on the final breakage stress of the specimen. The crack initiation and coalescence stresses during the crack propagation process are observed. The breakage process of the specimens is studied by inserting single and double cracks with different inclination angles at the center and applying uniaxial compressive stress at both ends of the specimen. The wing cracks are produced at the first stage of loading and start their propagation toward the direction of uniaxial compressive loading. The secondary cracks may also be produced in form of quasi-coplanar and/or oblique cracks in a stable manner. The secondary cracks may eventually continue their propagation in the direction of the maximum principle stress. The same specimens are numerically simulated by an indirect boundary element method known as displacement discontinuity method. Comparing some of the numerical and experimental results, one may validate the results given in this study. Проведено випробування на стиск циліндричних зразків із початковими тріщинами з
матеріалу типу гірських порід (пуцолановий портландцемент). Результати експериментальних вимірювань напруги, деформацій і характеристик міцності зразків показують, що наявність початкових тріщин і їх орієнтація не мають значного впливу на
величину границі міцності при стисканні. Досліджено зародження і злиття тріщин на
стадії їх росту. Процес руйнування зразків досліджували для випадків наявності в
їхній центральній частині одиночних або парних тріщин, що розташовані під різними
кутами, і прикладення одновісного стискального навантаження до обох торців зразка.
На першій стадії навантаження відмічалось виникнення стрілоподібних тріщин і їх
ріст у напрямку осі одновісного стискального навантаження. Окрім того, вторинні
тріщини з квазикомпланарною і (або) похилою конфігурацією характеризуються
стабільним ростом. У подальшому ці тріщини можуть розвиватися у напрямку
максимальних головних напружень. Виконано числовий розрахунок зразків із тріщинами за допомогою непрямого методу граничних елементів, тобто: методу розриву
переміщень. Порівняльний аналіз розрахункових і експериментальних результатів
підтверджує їх вірогідність. Проведены испытания на сжатие цилиндрических образцов с исходными трещинами из
материала типа горных пород (пуццолановый портландцемент). Результаты экспериментальных измерений напряжений, деформаций и характеристик прочности образцов показывают, что наличие исходных трещин и их ориентация не оказывают значительного влияния
на величину предела прочности при сжатии. Исследовано зарождение и слияние трещин на
стадии их роста. Процесс разрушения образцов исследовали для случаев наличия в их центральной части одиночных или парных трещин, расположенных под разными углами, и приложения одноосных сжимающих нагрузок к обоим торцам образца. На первой стадии нагружения наблюдалось возникновение стреловидных трещин и их рост в направлении оси
одноосной сжимающей нагрузки. Кроме того, для вторичных трещин с квазикомпланарной
и/или наклонной конфигурацией характерен стабильный рост. В дальнейшем эти трещины
могут развиваться в направлении максимальных главных напряжений. Выполнен численный
расчет образцов с трещинами с помощью непрямого метода граничных элементов, а именно:
метода разрыва перемещений. Сравнительный анализ расчетных и экспериментальных результатов подтверждает их достоверность.